The ENTRAMI technique: Endoscopic transgluteal minimal invasive technique for implantation of a pudendal electrode under full visual control: A cadaver study. Issue 1 (12th October 2018) - Jottard, Katleen; Bonnet, Pierre; Bruyninx, Luc; Ploteau, Stéphane; De Wachter, Stefan
Abstract : Aim: The aim of this article is to describe a minimal invasive trans gluteal endoscopic approach to implant a pudendal electrode for neuromodulation under full visual control. Methods: Eight trans gluteal approaches were performed on four cadavers. The sacral transforaminal percutaneous technique was performed to implant the electrode. The electrode was then picked up and placed under visual control next to the pudendal nerve. Results: The first trocar was placed in the upper lateral quadrant of the gluteal region. The 0° optical system was used to help with the pneumodissection to identify the sciatic nerve. At that point a second 3 mm trocar was placed to insert a dissecting grasping forceps. In some cases, a second 3 mm trocar was placed. A step by step dissection, based on anatomical findings, was necessary to be able to locate the pudendal nerve. The electrode, which was placed percutaneously and transforaminal through S3 or S4, was picked up and placed under full visual control next to the pudendal nerve, slightly entering the Alcock's canal. The electrode was placed in an ideal manner, meaning that all 4‐contact points of the electrode are in parallel and in contact with the targeted nerve. The electrode was fixed in that ideal position at the level of the sacrospinous ligament. After placement of that electrode, an X‐ray of the pelvic area was done. Conclusions: The ENTRAMI technique allows optimal pudendal electrode placement under full visual control and should now be tested in a clinical setting.